PWE-182 Dysmotility In Parkinson's Disease Correlates To Gut Symptoms: Findings Of A Wireless Motility Capsule Study. (9th June 2014) - Butt, SK; Leung, R; Bala, A; Bhatia, K; Raeburn, A; Emmanuel, A
Abstract : Introduction: Parkinson's disease (PD) is a neuro-degenerative disorder with frequent involvement of the gut. Symptoms arise throughout the gastrointestinal tract through dysmotility secondary to autonomic and enteric nervous system involvement, as well from skeletal muscle involvement in the oropharynx and anorectum. It has been speculated that gut involvement may precede motor symptoms. The Wireless Motility Capsule (WMC) yields data on transit and motility throughout the gut. We report the first use of WMC to systematically assess motility in PD patients with and without gut symptoms, compared to controls. Methods: 15 patients with established PD completed the study: eight (2 f, mean age 70 [47–85]) had GI symptoms and seven (2 f, mean age 61 [49–77]) did not based on history and baseline scores on the Gastroparesis Cardinal Symptom Index (GCSI) and Wexner constipation score. Data comparison with seven controls (3f, mean age 52 [39–63]). Medications affecting GI motility /pH were discontinued for the study and the WMC was ingested following a standardised nutrient bar meal. Data on gastric emptying time (GET), small bowel transit time (SBTT), colonic transit time (CTT) and whole gut transit time (WGTT) were calculated. Results: PD patients with gut symptoms showed significantly slower transit in the stomach (GET 5.2 vs. 2.7 h, p = 0.0003), colon (CTT 57.8 vs. 27.4 h, p = 0.02) and overall gut (WGTT 67.2 vs. 34.7 h, p = 0.02) compared to asymptomatic patients. Small Bowel transit (mean SBTT 4.17 h) did not significantly differ. GET, SBTT, CTT and WGTT did not differ between asymptomatic PD and controls. There was a significant correlation between the Wexner constipation score and CTT in all patients (p < 0.01), but no correlation between GCSI and gastric emptying (p > 0.05). Conclusion: This study demonstrates that symptomatic PD patients have markedly delayed transit times throughout the whole gut compared to asymptomatic PD patients and controls. The correlation between scores and transit times suggest that WMC is a less useful indicator of gastric emptying than small bowel and colonic transit. Disclosure of Interest: None Declared.